Using digital photography to document rectus femoris flexibility: A reliability study of the modified Thomas test. (May 2013) - Peeler, Jason; Leiter, Jeff
<x xml:space="preserve">Abstract</x> Background: Research indicates that rectus femoris muscle flexibility assessment techniques suffer from multiple sources of measurement error. Objective: To examine whether scoring of rectus femoris muscle flexibility from digital photographs of clinical examination using the modified Thomas test would be highly reliable. Methods: Twenty-eight individuals were digitally photographed while having their rectus femoris muscle flexibility evaluated using the modified Thomas test. Therapists were then asked to view these digital photographs and score participant's flexibility using modified Thomas test scoring criteria. A retest session was completed approximately 1-week later. Results: Kappa values for positive/negative scoring (intra-rater experienced X¯ = 0.86, in-experienced X¯ = 0.98; interrater experienced X¯ = 0.95, in-experienced X¯ = 0.99) and ICC values for goniometer scoring (intra-rater experienced X¯ = 0.98, in-experienced X¯ = 0.98; interrater experienced X¯ = 0.97, in-experienced X¯ = 0.98) indicated very high levels of reliability. Measurement error values (SEM = 1.0°, ME = 1.53°, and CV = 3%) and Bland and Altman plots (with 95% limits of agreement) further illustrated the very small degree of scoring variance. Conclusions: Results indicate that goniometer and positive/negative scoring of rectus femoris muscle flexibility from digital photographs of clinical examination using the modified Thomas test were highly reliable. This finding suggests that using digital photography as a means to document patient function during clinical examination may serve as a method to help standardize physical assessment, minimize error measurement, and assist the clinician/researcher in establishing whether an observed change between testing sessions is clinically significant.